URBAN RUINS: FRAGMENTS OF AN INNER FRESCO - Kertemelidou, Paraskevi (Design/Arts/Culture, 2020)
Having as starting point Lila Papoula’s exhibition ‘Walls That Were Hiding Our Faces’ at the Teloglion Foundation of Arts during the 2017 Thessaloniki Biennale of Contemporary Art, we examine her work under the prism of three main topics: as social documentary, as a familiar topos full of personal memories and nostalgia and as an architectural itinerary in the urban ruins of the old Athenian neighborhoods. In her compositions Lila Papoula does not merely present the urban ruins but rather she proposes a journey of self-discovery and a return to forgotten values, to activate memory for all of us. For Lila Papoula a derelict building is a ‘text’, an ‘image’ that determines its own materiality through what is inscribed into it. Papoula focuses on the thread of an interrupted life, on elements of a human absence which paradoxically still continues to exist and confirm life. In her paintings, based on the ‘photography transformed into painting’ technique, personal stories and the history of the contemporary city are interconnected and have acquired equal gravity.